Development of Mosquito Repellent, Antibacterial, Antioxidant and UV Protective Cotton Using a Novel Method of Azoic Dyeing with Terminalia Chebula - Ankit Singh; Javed Sheikh (Journal of Natural Fibers, 2022)
With rising awareness regarding human and environmental safety, the use of sustainable resources for the functionalisation of natural textile fibers are highly demanded. The present study investigates a novel process for the development of multifunctional cotton using the azoic dyeing method. Preparation of azoic dyes was performed using ethyl anthranilate (EA), a safe mosquito-repellent, and Terminalia chebula natural dye as the coupling component. The novel method of in-situ azoic dyeing using Terminalia chebula and ethyl anthranilate for functional coloration of cotton is explored. The developed shades were found satisfactory in terms of fastness and color strength. The novel method resulted in mosquito-repellent cotton with 100% mosquito repellency, which was found durable until at least 20 washes. Additional functional properties such as antibacterial activity (more than 94%), antioxidant activity (>87%) and UV protection (UPF >50) were also confirmed.